KAJIAN TEKNIS DAN FINANSIAL USAHA BUDIDAYA IKAN SISTEM KERAMBA JARING APUNG PADA PERAIRAN TELUK AMBON (KASUS KJA MILIK SUPM AMBON) - Stevanus M. Siahainenia; Bawole Bawole; Petrus D. Siahaya (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2021)
Ambon Bay is designated as a marine cultivation development area based on the allocation of RZWP3K space contained in the Maluku Regional Regulation Number 01 of 2018. The cultivation activities carried out by the Ambon SUPM (Maluku Fisheries Business School) institution uses a floating net-netting system, intended for training students as well as business facilities. The research objective, to describe the technical production of the KJA system; analyze business finances including expenses and income as well as financial ratios. The survey was conducted from March to May 2020, using a questionnaire approach to obtain primary data. Saturated sampling technique is used considering the number of samples is only 3 units of marine cage. The respondents used were key informants, namely the KJA managers. The results showed that the construction of the marine cage was made of HDPE with the same size for the three units. Production of grouper, pompano and snapper, respectively 700, 850, and 800 kg / cultivation period. Average expenditures reached Rp. 31,257,524 / cultivation period and an income of Rp. 56,242,476. ROI ratio for KJA units I, II, and III each of 29.50%; 30.80%, and 28.90%; the R / C ratios were 2.12, 2.99, and 2.93, respectively. BEP (unit) and BEP (price) for each KJA: unit I, 393 kg and Rp. 31,850; unit II, 443 kg and Rp. 24,306; while unit III, 419 kg and Rp. 24,450.